HETEROMORPHA ARBORESCENS: A REVIEW OF ITS BOTANY, MEDICINAL USES, AND PHARMACOLOGICAL PROPERTIES - Maroyi, Alfred (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Heteromorpha arborescens is an important medicinal plant species throughout its distributional range in tropical Africa. This study evaluated the botany, medicinal uses, and pharmacological activities of H. arborescens. Literature focusing on the botany, phytochemical, pharmacological, and toxicological properties of H. arborescens were obtained from scientific databases such as SCOPUS, Science Direct, PubMed, SciFinder, Medline, and Google Scholar. Pre-electronic literature sources such as book chapters, books, journal articles, conference papers, and other scientific documents were obtained from the University library. Literature search revealed that H. arborescens is used as an aphrodisiac, as herbal medicine for shortness of breath, intestinal worms, inflammation, pain, respiratory problems, skin infections, headache, fever, and malaria. Pharmacological studies of compounds and H. arborescens extracts revealed anthelmintic, antiarthritic, antibacterial, antifungal, anti-inflammatory, antimycobacterial, antinociceptive, antioxidant, antipeptic ulcer, anti-scabies, antispasmodic, antiviral, cytotoxicity, genotoxicity, and uterotonic activities. More detailed research is needed aimed at assessing phytochemical, pharmacological, and toxicological properties of different plant parts and phytochemical compounds isolated from the species.